Obstructive sleep apnea in Down syndrome: Benefits of surgery and noninvasive respiratory support. Issue 8 (24th May 2017) - Dudoignon, Benjamin; Amaddeo, Alessandro; Frapin, Annick; Thierry, Briac; de Sanctis, Livio; Arroyo, Jorge Olmo; Khirani, Sonia; Fauroux, Brigitte
Abstract : Children with Down syndrome are at increased risk of obstructive sleep apnea (OSA). The aim of the study was to describe the management of OSA in a large cohort of children with Down syndrome. A retrospective analysis of sleep studies and consequent management was performed for all consecutive Down syndrome patients evaluated between September 2013 and April 2016. The data of 57 patients were analyzed: 51/53 had an interpretable overnight polygraphy and 4 the recording of nocturnal gas exchange. Mean age at baseline sleep study was 6.2 ± 5.9 years. Eighteen patients (32%) had prior upper airway surgery. Mean apnea‐hypopnea index (AHI) was 14 ± 16 events/hr with 41 of the 51 (80%) patients having OSA with an AHI >1 event/hr and 20 patients (39%) having an AHI ≥10 events/hr. Consequently, eight patients (14%) had upper airway surgery. OSA improved in all patients except two who needed noninvasive respiratory support. Nineteen (33%) patients required noninvasive respiratory support. Mean age at noninvasive respiratory support initiation was 7 ± 7 years. On 11 patients with objective adherence data available, mean compliance at 2 ± 1 years of treatment was excellent with an average use per night of 8 hr46 ± 3 hr59 and 9 patients using the noninvasive respiratory support >4 hr/night. Noninvasive respiratory support was associated with an improvement of nocturnal gas exchange. The prevalence of OSA is high in Down syndrome. Upper airway surgery is not always able to correct OSA. Noninvasive respiratory support represents then an effective treatment for OSA and good compliance may be achieved in a majority of patients.